WATER DISCHARGE MEASURING INSTRUMENTS: AN UP TO DATE OVERVIEW (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Technological progress could not but affect the sphere of hydrometric measurements. New instruments have been implemented to add to such traditional measuring instruments as mechanical current meters or to replace them. Over the past 20 years, the number of different types measuring instruments has increased dramatically. That is why the analytical review and classification of these devices are needed to help with making appropriate management decisions in the field of streamflow monitoring and surveys. The article presents the multivariable classification of measuring instruments, based on such factors as: morphology scaling (channel width and depth), measuring conditions (open, weed or ice-covered channel), logistical factor (mobile or stationary) and required accuracy. Characteristics of each type of measuring instruments were also considered and the limitations of their applicability were described. The results presented in the paper are expected to expand the horizons of approaches used for estimation of water discharge.